Current Status of the Effect of Seawater Ions on Copper Flotation: Difficulties, Opportunities, and Industrial Experience. (4th July 2022) - Cruz, Constanza; Botero, Yesica. L.; Jeldres, Ricardo I.; Uribe, Lina; Cisternas, Luis A.
ABSTRACT: The limited availability of conventional water resources and inefficient water management has resulted in seawater use in the flotation process of copper sulfide ores at several concentrator plants. The flotation process in seawater is complex and multifaceted, as its chemistry is different compared to fresh water. This article presents the current status of the effect of seawater ions on flotation of copper sulfides ores, aiming to identify the main difficulties and opportunities related to this issue. This article also presents the current industrial experience of the flotation of copper sulfide ores with seawater and possible solutions to improve their performance.